Life 3.0 : being human in the age of artificial intelligence - Tegmark, Max (New York : Alfred A. Knopf, 2017)
"What jobs should be automated? How should our legal systems handle autonomous systems? How likely is the emergence of suprahuman intelligence? A.I. is the future of science, technology, and business--and there is no person better qualified or situated to explore that future than Max Tegmark. What has A.I. brought us? Where will it lead us? The story of A.I. is the story of intelligence--of life processes as they evolve from bacteria (1.0) to humans (2.0), where life processes define their own software, to technology (3.0), where life processes design both their hardware and software. We know that A.I. is transforming work, laws, and weapons, as well as the dark side of computing (hacking and viral sabotage), raising questions that we all need to address: What jobs should be automated? How should our legal systems handle autonomous systems? How likely is the emergence of suprahuman intelligence? Is it possible to control suprahuman intelligence? How do we ensure that the uses of A.I. remain beneficial? These are the issues at the heart of this book and its unique perspective, which seeks a ground apart from techno-skepticism and digital utopia"--
"This is a Borzoi Book published by Alfred A. Knopf."
Includes bibliographical references and index.
Keywords: Artificial intelligence -- Philosophy; Artificial intelligence -- Social aspects; Automation -- Social aspects; Artificial intelligence -- Moral and ethical aspects; Automation -- Moral and ethical aspects; Artificial intelligence -- Philosophy; Technological forecasting; TECHNOLOGY & ENGINEERING / Robotics; SCIENCE / Experiments & Projects; TECHNOLOGY & ENGINEERING / Inventions